ChemInform Abstract: Copper‐Catalyzed Regioselective Intramolecular Oxidative α‐Functionalization of Tertiary Amines: An Efficient Synthesis of Dihydro‐1, 3‐Oxazines. Issue 8 (25th February 2014) - Deb, Mohit L.; Dey, Suvendu S.; Bento, Isabel; Barros, M. Teresa; Maycock, Christopher D.
Abstract The hydroxy functional group directs the α‐functionalization of tertiary amines, synthesizing 1, 3‐oxazines by C—O bond formation.